2017
DOI: 10.4172/clinical-investigation.1000108
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, safety and costs of labor induction with intravaginal misoprostol versus dinoprostone vaginal insert

Abstract: Background: Over the last decade, a lot of clinical reviews have been published, but they are heterogeneous and present disparity of outcomes. The best choice for inducing labor is not clear today. The objective of the study is to compare misoprostol with dinoprostone for labor induction including obstetrical and neonatal outcomes, side effects and costs. Methods and findings:From September 2012 to December 2013 a retrospective observational study was performed, including all pregnant women with medical indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The mean percentage of induced labour is in the range of about 20-25 percent, which signifies that every fifth pregnant woman is qualified to pregnancy termination before the onset of spontaneous uterine contractions [9]. In our material, this percentage was similar and did not differ from the data of other authors.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The mean percentage of induced labour is in the range of about 20-25 percent, which signifies that every fifth pregnant woman is qualified to pregnancy termination before the onset of spontaneous uterine contractions [9]. In our material, this percentage was similar and did not differ from the data of other authors.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, in the studies by Yehia et al [20], no statistical differences were observed in the occurrence of uterine hyperstimulation in the groups of women undergoing induction with misoprostol and dinoprostone, which may be due to differences in the form and dose of drugs used: titrated oral misoprostol (20 mcg every 2 hours) and vaginal dinoprostone (3 mg). Other studies compared oral misoprostol (50mcg every 4 hours), vaginal misoprostol (25-50mcg every 6 hours) with vaginal gel dinoprostone [23] or vaginal insert dinoprostone (10 mg) [9]. In all the studied groups, the authors did not find statistically significant differences in the occurrence of tachysystole and uterine hyperstimulation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In group I, mean preinduction Bishop score was 2.18 whereas 2.5 in Chia et al 4 and Cazorla et al 16 study, 3.1 in Ghanaie et al 17 study. In group II, mean preinduction Bishop score was 2.95 whereas it was 2.9 in the study by Henry et al 18 and it was 4.2 in the study by Young et al 14 study.…”
Section: Discussionmentioning
confidence: 79%